First-time fathers' experience of childbirth: a cross-sectional study. (December 2021) - Franzen, Jessica; Cornet, Isabelle; Vendittelli, Françoise; Guittier, Marie-Julia
Highlights: First time fathers's experiences of childbirth are associated with important worry. First time fathers need more professional support to foster positive experiences of childbirth. Implementing specific antenatal classes for fathers could support the fatherhood process. Prenatal preparation and information are positive factors linked with fathers' experiences. Abstract: Objectives: The purposes of this study are to report first-time fathers' experiences of childbirth through three dimensions (professional support, worries and prenatal preparation) and to analyse the influence of sociodemographic, antenatal and obstetrical factors on the three dimensions. Setting: Participants were recruited in France and Switzerland from two university hospitals that routinely manage high-risk pregnancies (level 3 – perinatal care level), with 4, 000 to 5, 000 annual births each. Methods: This is a secondary analysis of a cross-sectional study. The data initially were collected for the cross-cultural validation of the First-Time Father Questionnaire (FTFQ) into French. Descriptive statistics were used to report the participants' characteristics and their questionnaire responses. Multivariate linear regression analysis was carried out to stress the positive or negative factors linked with fathers' experiences of childbirth. Findings: Among 350 first-time fathers, 160 completed the FTFQ (response rate of 45.7%). The average age of the participants was 33 years old. We observed 12 questionnaire items with more than 20% unfavourable responses, seven of which involved the measurement of the worry dimension. Antenatal education and the prenatal-preparation dimension were positive factors linked with fathers' experiences. In addition, 57% of participants reported using one means of antenatal education, and 45% accessed information from family or friends. Conclusions and implications for practice: The results suggest that first-time fathers need more professional support to foster positive experiences of childbirth. Their experiences of childbirth are associated with considerable worry. Antenatal classes specifically for fathers could reduce this worry and support the fatherhood process. Research should be carried out on these topics.